Nasledniki - Kozlov, Sergeĭ, 1966-; Odegov, Konstantin, 1959-; I͡Urchenko, Pasha (Studio Pressing, 2008)
The film features the life of a teenager boy who lives in the remote taiga settlement. Having been born in an ordinary family of an oil-field driller and a nurse, the boy is a successful schoolboy. Each summer the family goes to the Crimea to visit the boy's grandmother. Their quiet life is ruined when the father faces troubles, caused by his job. He starts drinking and addicts his wife to it. The teenager is left on his own. Moreover, he is obliged to sell stolen things. Suddenly he gets hold of an object that gives a new direction to the life of the family. --